A Novel Split-Course High-Dose Palliative Radiotherapy Regimen for Locally Advanced Sinonasal Cancer: A Case Report - Saif Aljabab; Amna Mohaimeed; Firas AlMomen; Abdullah AlSwailem; Yasir Alayed (Case Reports in Oncological Medicine)
Sinonasal malignancies (SNMs) are rare heterogeneous malignancies that frequently present with locally advanced disease. The prognosis is poor when the disease is considered extensive and unresectable. In such cases, a high-dose palliative radiotherapy regimen is often required, but the ideal dose and fractionation have not been established. We detail a 33-year-old male who initially presented with a progressively growing mass over the right cheek. A biopsy of the lesion revealed squamous cell carcinoma (SCC). Imaging revealed a very advanced and unresectable disease with the involvement of several head and neck subsites. He progressed further after receiving induction chemotherapy from an outside institution. The patient requested prompt tumor and symptom control to travel back to his home country. We offered him high-dose split-course palliative radiotherapy in the form of a quad Shot of 14.80 Gy in four fractions twice daily, followed by 30 Gy in five fractions every other day with a 2-week interval. Treatment resulted in excellent clinical response with symptomatic relief in a short time, and the patient could travel back home safely.